Peran Strategi Pemasaran Untuk Meningkatkan Omset Penjualan Di Pt. Indomarco Primatama Tbk. (Store Indomaret Kalen) - Sri Wahyuni; Sudiah Hestianah; Adam Nur Muhammad (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2022)
Indomaret is a real form of rapid economic development in the activities ofcompanies engaged in trade. Indomaret is widespread with very diversemarketing strategies. Starting from selecting locations, setting prices,promotions, to offering facilities and services that make customers feelcomfortable. This is also done at Indomaret Kalen in order to increase dailysales turnover. At Indomaret Kalen, various types of efforts are made toincrease sales turnover, marketing strategies are carried out as best aspossible to provide maximum results. However, sometimes Indomaret Kalenexperiences problems in implementing this marketing strategy, includingdeclining product quality and prices that are less affordable according to customer assumptions. To overcome these obstacles, Indomaret Kalenevaluates and analyzes market trends, creates product innovations,strengthens customer service, and creates product bundling promotions sothat the sales process does not face major losses and risks.